Fruit quality trait discovery and metabolic profiling in sweet cherry genebank collection in Greece. (16th April 2021) - Karagiannis, Evangelos; Sarrou, Eirini; Michailidis, Michail; Tanou, Georgia; Ganopoulos, Ioannis; Bazakos, Christos; Kazantzis, Konstantinos; Martens, Stefan; Xanthopoulou, Aliki; Molassiotis, Athanassios
Highlights: Twenty-two sweet cherry accessions from Greek germplasm collection were analyzed. Various quality features and bioactive compounds of fruits are identified. Tsolakeika and Vasiliadi displayed the higher consumer acceptance. 'Vasiliadi', 'Tragana Edessis-Naousis' and 'TxAg33' contained high polyphenols. This study may contribute to breeding programs for high-quality cherries. Abstract: The current study characterizes the physicochemical, sensory and bioactive compound traits of twenty-two sweet cherry accessions, namely breeding lines, landraces and modern cultivars, embodying the majority of Greek germplasm. The evaluated accessions differ in several quality traits including colour parameters and textural properties as well as sensory attributes, such as taste intensity and overall acceptance. Significant differences in primary metabolites, including fructose, glucose, sorbitol, malic acid were recorded among tested accessions. All genotypes were rich in polyphenols, primarily in quercetin-3, 4- O -diglucoside, esculetin, rutin and neochlorogenic acid. An anthocyanins-related discrimination among accessions was also obtained based on cyanidin-3- O -rutinoside and peonidin glycosides content. Overall, the cultivars 'Tsolakeika' and 'Bakirtzeika' exhibited the higher consumer acceptance while the cultivars 'Vasiliadi' and 'Tragana Edessis-Naousis' and especially the breeding line 'TxAg33' contained high polyphenol levels. These results represent a valuable resource for future breeding efforts for sweet cherry cultivars with improved nutritional quality traits.